A Preliminary Study on Biodegradability of Alkyl Ketene Dimer-Treated All-Cellulose Composites - Zakir, Nur Zafirah; Mat Salleh, Mokhtar (Advanced and Sustainable Technologies (ASET), 2026)
Cellulose is the most abundant natural organic polymer on Earth. It has been widely used to develop cellulose-based materials that can be tailored to exhibit tunable properties, including mechanical and physical properties, electrical conductivity, and other unique characteristics by incorporating additional functional components. Nowadays, a new class of monocomponent composites based on cellulosic materials, known as all-cellulose composites (ACCs), has attracted considerable interest among researchers. However, the hydrophilic nature of cellulose weakens its physical and mechanical properties due to the presence of numerous hydroxyl groups. Therefore, alkyl ketene dimer (AKD) was incorporated into the development of ACC to mitigate increased water absorption. Few studies have been reported on the physical and mechanical properties of AKD-treated ACC. However, no studies have addressed its biodegradation behavior. This study aims to investigate the role of AKD and the influence of temperature during soil burial testing on the biodegradation of AKD-treated ACC. The results indicated that AKD-treated ACC did not experience any degradation at either room temperature or 40°C, with negligible mass loss observed after 49 days of soil burial testing. In contrast, ACC exhibited surface discoloration and fiber loosening after burial. The mass loss for ACC was recorded as 4.6 and 12.2% at room temperature and 40°C, respectively. These findings suggest that the hydrophobic nature of AKD may impede ACC biodegradation. This study also relates to the Sustainable Development Goals (SDGs), including SDGs 6, 9, and 12-15.